STUDI KOMPARASI KEMAMPUAN MEMBACA AL-QUR’AN BERDASARKAN LATARBELAKANG P ENDIDIKAN SISWA KELAS VIII DI SMP NEGERI 40 PALEMBANG - Amelia Agustina; Muhammad Isnaini; Nyayu Soraya (PAI RAFAH, 2021)
In State Junior High School 40 Palembang, they have different educational backgrounds. Consists of students graduating from Islamic High Boarding School (MI) and students graduating from Elementary School (SD). In schools, especially in the subject of Islamic Religious Education between Elementary School and Islamic High Boarding School there are differences. namely the allocation of time and religious material. The existence of different educational backgrounds will certainly provide different support and obstacles.Researcher wanted to compare the reading ability of the Al-Qur'an of Islamic High Boarding School and Elementary School graduate students with the title "Comparative Study of Al-Qur'an Reading Ability Based on Educational Background of Class VIII Students in 40 State Junior High Schools in Palembang" This study aims to determine whether there are differences in the ability to read the Qur'an between students graduating Islamic High Boarding School and elementary school graduates in State Junior High School 40 Palembang.The population in this study were all students of class VIII in Palembang 40 State Junior High School in 2019-2020, totaling 336 students, consisting of 20 Islamic High Boarding School graduates and 316 elementary school graduates. Population a sample of 20 MI graduates and 20 elementary school graduates was taken. And for data analysis techniques using the "t" test formula.Hypothesis testing obtained because t0 is obtained with the acquisition of 3.01 then for tt = 2.02 and 2.70, for that t0 is said to be greater than tt, Nor of 5% or 1%, with the result: 2.02 <3 , 01> 2.70. So it can be concluded that there is a significant difference in the ability to read Al-Qur'an of students between Islamic High Boarding School (MI) graduates and Elementary School (SD) graduates in class VIII in State Junior High School 40 Palembang.